2014
DOI: 10.1016/j.paid.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

It takes more than one for parenting: How do maternal temperament and child’s problem behaviors relate to maternal parenting behavior?

Abstract: The current study examined how individual differences in maternal temperament and child problem behaviors correlate with observed maternal positivity and negativity toward the child. The sample consisted of 153 mothers of 3-to-7 year old children. Mothers reported their own temperament (surgency, orienting sensitivity, effortful control and negative affect) and their children's problem behaviors. Maternal behavior was videotaped in a set of structured interaction tasks with the child during a lab visit. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This finding is in line with a substantial body of 19 Running head: PREDICTORS OF PARENTING research (e.g., Atzaba-Poria et al, 2014;Clark, Kochanska, & Ready, 2000;Spinath & O'Connor, 2003) and is a useful reminder to practitioners that mothers who struggle to manage their emotions are also likely to struggle to form rewarding relationships with their children. As mothers continue to be more involved in childrearing (as measured in terms of time spent present with children as well as actively engaged with children) than are fathers (Lamb, 2010), they shoulder more responsibility for childcare tasks (e.g., taking children to and from school, keeping dentist appointments).…”
Section: Mothers Versus Fatherssupporting
confidence: 78%
See 1 more Smart Citation
“…This finding is in line with a substantial body of 19 Running head: PREDICTORS OF PARENTING research (e.g., Atzaba-Poria et al, 2014;Clark, Kochanska, & Ready, 2000;Spinath & O'Connor, 2003) and is a useful reminder to practitioners that mothers who struggle to manage their emotions are also likely to struggle to form rewarding relationships with their children. As mothers continue to be more involved in childrearing (as measured in terms of time spent present with children as well as actively engaged with children) than are fathers (Lamb, 2010), they shoulder more responsibility for childcare tasks (e.g., taking children to and from school, keeping dentist appointments).…”
Section: Mothers Versus Fatherssupporting
confidence: 78%
“…Parenting young children is a stressor particularly likely to highlight individual differences in proneness to anger (Atzaba-Poria, Deater-Deckard, & Bell, 2014;Belsky & Barends, 2002;Deater-Deckard, 2004) and was moderately associated with parenting quality in our sample during middle childhood . Finally, we focus on a key contextual feature of the family -household chaos.…”
Section: Running Head: Predictors Of Parentingmentioning
confidence: 70%
“…Regarding the moderation effects, note that variables in the models are always interchangeable statistically (e.g., Atzaba‐Poria, Deater‐Deckard, & Bell, ; Shannon, Beauchaine, Brenner, Neuhaus, & Gatzke‐Kopp, ). The current study focused on the father's role.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, genetic factors impact both temperament and behavior [ 40 , 41 ]. Secondly, parental behaviors do not exert an unidirectional impact on child behavior, instead child temperament and response influence the child-parent interaction [ 14 , 15 ]. Rettew et al (2006) showed that the interaction between parent and child temperament dimensions predicted higher levels of child internalizing and externalizing problems than the traits alone [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on adult patients with borderline personality disorder, mothers of patients were found to display lower levels of self-directedness, while fathers displayed higher levels of novelty seeking, harm avoidance and self-transcendence and lower levels of self-directedness compared to control subjects [ 13 ]. Moreover, interactions between parental and child traits might influence effects on child behavior [ 14 , 15 ]. Rettew et al (2006), found the combination of high maternal and child novelty seeking to be associated with child attention problems, and similarly high harm avoidance in fathers and children were associated with child internalizing problems [ 15 ].…”
Section: Introductionmentioning
confidence: 99%